2005
DOI: 10.3233/nre-2004-19409
|View full text |Cite
|
Sign up to set email alerts
|

How vegetative is the vegetative state? Preserved semantic processing in VS patients – Evidence from N 400 event-related potentials1

Abstract: Event-related potentials (ERPs) can provide valuable information about cognitive capabilities in severely braindamaged patients. This study examined 120 patients with severe brain damage using event related potentials ERPs (N 400) to gain information about their remaining semantic processing capabilities and to contribute to differential diagnosis. Patients were classified into three diagnostic groups: patients in vegetative state (VS), patients in near vegetative state (NEVS) and patients not in vegetative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
26
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 68 publications
(32 citation statements)
references
References 5 publications
6
26
0
Order By: Relevance
“…For the N400, present numbers are similar to those of Kotchoubey et al and Schoenle and Witzke, who found an N400 in 14 to 39% of UWS patients, with the rates depending on assessment criteria and stimulus complexity. In line with the present pattern, across studies, more patients are identified with late ERPs when computerized analysis techniques are used, suggesting, perhaps contrary to common intuition, that clinicians use more conservative assessment criteria than current implementations of automated algorithms. This may be due to human raters taking into account overall data quality, discounting local differences even if they might be statistically significant, if they occur for example in the context of continuous high‐voltage discharges.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…For the N400, present numbers are similar to those of Kotchoubey et al and Schoenle and Witzke, who found an N400 in 14 to 39% of UWS patients, with the rates depending on assessment criteria and stimulus complexity. In line with the present pattern, across studies, more patients are identified with late ERPs when computerized analysis techniques are used, suggesting, perhaps contrary to common intuition, that clinicians use more conservative assessment criteria than current implementations of automated algorithms. This may be due to human raters taking into account overall data quality, discounting local differences even if they might be statistically significant, if they occur for example in the context of continuous high‐voltage discharges.…”
Section: Discussionsupporting
confidence: 90%
“…This wide range has been ascribed to variations in stimulus complexity or emotionality, heterogeneity in patients' etiology, current diagnosis, and different ERP analysis techniques . For the N400, present numbers are similar to those of Kotchoubey et al and Schoenle and Witzke, who found an N400 in 14 to 39% of UWS patients, with the rates depending on assessment criteria and stimulus complexity. In line with the present pattern, across studies, more patients are identified with late ERPs when computerized analysis techniques are used, suggesting, perhaps contrary to common intuition, that clinicians use more conservative assessment criteria than current implementations of automated algorithms.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations